Patterns of Drug Utilization in Cardiology Department of a Tertiary Level Hospital in Bangladesh - Afroj, Farhana; Parveen, Feroza; Ara, Ferdous; Iqbal, Md Jalal Uddin; Saha, Rekha Rani; Rozario, Rini Juliet (Bangladesh Journal of Physiology and Pharmacology, 2014)
A cross-sectional descriptive study was carried out among patients admitted in cardiology department from 1st January to 31st March 2011 in Sir Salimullah Medical College & Mitford Hospital, Dhaka to see the patterns of prescriptions and use of drug by using WHO core drug use indicators and some additional indices. A total of 300 patients were included in this study. The average number of drugs per encounter was 8.8 and 11.43% drugs were prescribed by generic name. Percentage of encounters with cardiovascular drugs were 64%,other drugs were 36% and 25% injection were prescribed.70.45% drugs were prescribed from EDL of Bangladesh, the availability of copy of essential drug list was present and availability of key drugs was 74%.So the results of the present study may contribute to identify essential drug prescribing patterns in our country. DOI: http://dx.doi.org/10.3329/bjpp.v28i1-2.20072 Bangladesh J Physiol Pharmacol 2012; 28(1&2):1-4